2018
DOI: 10.1007/s00268-018-4595-9
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Non‐operative Management of Penetrating Cervical Venous Trauma is Safe and Effective

Abstract: SNOM is applicable to a well-defined subset of patients with isolated penetrating cervical venous trauma to the IJV and SCV identified on CTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 27 publications
0
26
0
2
Order By: Relevance
“…However, no studies have reported on the endovascular evaluation of the venous system in penetrating neck trauma. 4 To the best of our knowledge, the present study is the first to report a total endovascular approach to penetrating trauma to zone II of the neck. This novel approach was developed by the senior author (E.A.).…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…However, no studies have reported on the endovascular evaluation of the venous system in penetrating neck trauma. 4 To the best of our knowledge, the present study is the first to report a total endovascular approach to penetrating trauma to zone II of the neck. This novel approach was developed by the senior author (E.A.).…”
mentioning
confidence: 71%
“…However, none the patients in the series underwent endovascular treatment. 4 In our patient, we were able to image all three segments of the venous system to exclude a penetrating injury without resorting to open operative management. Had significant venous injury been identified, traditional open neck exploration would have been warranted to appropriately address the injury.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many international studies lack the significant numbers of patients seen in the south african trauma setting [1][2][3][4][5][6][7][8][9][10][11][12]. Madsen et al, published several studies focusing on penetrating neck injuries in the Pietermaritzburg metro area [13][14][15][16]. studies from cape town have also been published analysing the incidence and results of patients with penetrating neck trauma including the use of balloon tamponade [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Las venas constituyen las estructuras más comprometidas en lesiones penetrantes de cuello, pudiendo tener un manejo no quirúrgico selectivo, en comparación con las arteriales, que no ceden en su sangrado debido a la presión de las arterias 6 . El trauma laringotraqueal es igualmente raro, aproximadamente 1 caso por cada 30,000 pacientes que ingresan al Servicio de Urgencias.…”
Section: Introductionunclassified